Technological innovations enhance invasive species management in the anthropocene. (19th April 2023) - Fricke, Rachel M; Olden, Julian D
Abstract: Curbing the introduction, spread, and impact of invasive species remains a longstanding management and policy prerogative. In recent decades, globalization and environmental change have further complicated efforts to execute science-based actions that address these challenges. New technologies offer exciting opportunities to advance invasion science knowledge, enhance management actions, and guide policy strategies but are increasingly complex and inaccessible to most practitioners. In the present article, we offer a synthetic perspective of innovative technologies with applications for invasive species management related to pathway intervention, spread prevention, impact mitigation, and public engagement. We also describe tools that augment big data processing required by some methods (e.g., remote sensing, mobile application data), such as automated image and text recognition built on machine learning. Finally, we explore challenges and opportunities for successful integration of emerging technologies into invasive species management, focusing on pipelines that enable practitioners to integrate tools into practice while recognizing logistic and financial constraints.